PERANCANGAN BUSANA GENDERLESS FASHION BERDASARKAN ANALISIS PREFERENSI DAN PERSEPSI GENDER PADA DEWASA AWAL - Kamilia, Alya Izza; Ratuannisa, Tyar (Universitas Ciputra Surabaya, 2024)
The continuous development of technology and information flow has brought about significant shifts in the dynamics of life, including changes in culture, values, and social norms in today's era. This transformation also impacts the fashion industry, which is an integral part of society's appearance and lifestyle. The phenomenon of genderless fashion trends exemplifies a significant change in the contemporary fashion landscape. Genderless fashion expands perspectives on gender and creates space for individual expression without rigid gender boundaries. However, in Indonesia, this trend faces challenges in acceptance by a society that predominantly adheres to patrilineal cultural values. Through a qualitative phenomenological research approach, this study aims to design and generate recommendations for genderless fashion clothing forms that are responsive and relevant based on the analysis of preferences and gender perceptions among young adults in Indonesia. Additionally, this research aims to identify and evaluate factors influencing the acceptance of genderless fashion clothing among young adults in Indonesia, particularly concerning the essence and role of genderless fashion trends. By considering issues such as ethics, sustainability, and inclusion, this research is expected to provide insights into the industry regarding the relevance and urgency of these issues amid current social developments and fashion trends. Thus, this research is expected not only to contribute to the academic domain but also to serve as a bridge for educating and fostering open dialogue among the wider society and unraveling its current complexities. The findings of this research will provide significant benefits to researchers, academics, designers, the fashion industry, and society as a whole. It is hoped that this research will serve as a valuable guide in designing more inclusive and relevant genderless fashion clothing aligned with current social values and fashion trends, thereby enhancing understanding and acceptance of the genderless fashion concept in Indonesia.